Isolasi dan Identifikasi Jamur pada Buah Cabai Rawit Putih (Capsicum frutescens L.) Varietas Hibrida F1 Bhaskara yang Bergejala Antraknosa dari Lahan Tani Desa Tondoh Kabupaten Kutai Barat - Riska Rahmawati Utami; Sonja Verra Tinneke Lumowa; Masitah Masitah; Suparno Putera Makkadafi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Anthracnose is a disease that often attacks cayenne pepper (Capsicum frutescens L.). This study aims to identify fungal species and determine the morphological characteristics of fungi found in white cayenne pepper fruit of the F1 Bhaskara Hybrid variety with anthracnose symptoms from the farmland of Tondoh Village, Mook Manaar Bulatn District, West Kutai Regency. The type of research used is qualitative descriptive, namely symptomatic fruit samples were isolated using the direct planting method (direct plating) on ​​Potato Dextrose Agar (PDA) media, and fungal identification was carried out by observing the macromorphological and micromorphological characteristics of the fungus. The results showed that there were three types of fungi that were successfully isolated, namely Colletotrichum sp., Pythium sp., and Rhizoctonia sp. Colletotrichum sp. has white colonies with a cotton-like texture, septate hyphae, and cylindrical conidia. Pythium sp. is characterized by non-septate hyphae and spherical sporangia. Rhizoctonia sp. have light brown colonies with septate hyphae and perpendicular branches forming approximately 90° angles. The presence of these three fungi indicates that in addition to Colletotrichum sp. as the primary cause of anthracnose, there are accompanying pathogens that exacerbate damage and accelerate fruit decay. The results of this study serve as the basis for developing anthracnose control strategies.